Investigating the relationship between cultural intelligence and knowledge management with organizational agility in Tehran province relief committee - Shamloo, Zahra; Nazem, Fattah (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2021)
Background and purpose: It seems that identifying the dimensions and actions of knowledge management and cultural intelligence in agile organizations on the one hand and examining their relationship with the actions and dimensions of agility on the other hand, is an undeniable necessity in the organization; Therefore, the present research was conducted with the aim of investigating the relationship between cultural intelligence and knowledge management with organizational agility in the Imam Khomeini Relief Committee of Tehran province. Methodology: The current research was a correlational descriptive study. The statistical population was all employees of the Imam Khomeini Relief Committee of Tehran province. Simple random sampling was done by preparing a list of 200 sample employees, and cultural intelligence questionnaires by Erli and Ang (2004), Newman and Konrad (2000) knowledge management, and Chabaki Sharifi and Zhang (2004) organizational questionnaires were implemented. Findings: The results showed that there is a significant relationship between cultural intelligence and knowledge management with organizational agility. Also, a significant relationship was found between knowledge (cognition), motivational and behavioral components and organizational agility, and among the dimensions of knowledge management, the two dimensions of knowledge preservation and knowledge creation have a significant relationship with organizational agility. Conclusion: The results of this research showed that cultural intelligence and dimensions of knowledge (cognition), motivational and behavioral as well as knowledge management and the two dimensions of knowledge preservation and knowledge creation could predict organizational agility.